Kemiskinan di Kota Pekalongan (Studi Etnografi di Empat Kampung) - Hidayat, Manarul; Rachman, M. Erika; Kurniali, M. Haidar Fikri; I'tisham, M. Rayhan; Nugraha, Rangga Setya; Ida Gunawati, Amalia; Kartika Dewi, Mutiara (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2024)
Poverty in the City of Pekalongan should be viewed as urban poverty, whose vulnerability is a social construct. This study was conducted on four priority communities to explain poverty in this city, namely: the fishing community in Kampung Pegirian, the farming community in Kampung Yosorejo, the batik labor community in Kampung Jenggot Tengah, and the informal worker community in Kampung Nggodang. Using ethnographic methods, this study addresses the types of social relations that occur in productive activities, which ultimately create poverty rather than prosperity. The study results, interpreted through Henry Bernstein's political economy perspective, indicate that the dynamics of poverty in the City of Pekalongan are constructed through ecological conditions, modes of production, social relations of production, and developmental interventions. Keywords: Poverty, fishermen, farmers, batik workers, informal workers